Heparin-binding Hemagglutinin of Mycobacterium tuberculosis Is an Inhibitor of Autophagy - Zheng, Qing; Li, Zhi; Zhou, Shan; Zhang, Qian; Zhou, Lei; Fu, Xiaorui; Yang, Liu; Ma, Yueyun; Hao, Xiaoke (Frontiers in Cellular and Infection Microbiology, 2017)
Airway epithelial cell is often the initial site of attack by pathogens, and cell death is commonly caused by internalization of Mycobacterium tuberculosis (Mtb). However, the mechanism of interaction between epithelial cells and Mtb is not well understood. In this study, we investigated the role of the heparin-binding hemagglutinin (HBHA) protein of Mtb in the function of epithelial cells. In particular, the autophagy of A549 cells was determined based on microtubule-associated protein 1 light chain 3 alpha (LC3) activity. Autophagosome formation was detected by Monodansylcadaverine (MDC) staining and immune fluorescence staining of LC3. Autophagy could be significantly suppressed by HBHA protein. In addition, the LDH assay results showed that HBHA treatment could induce death on A549 cells. To explore the form of cell death, we detected the activity of caspase-3 and LDH release of A549 cells in the presence or absence of caspase inhibitor Z-VAD-FMK. Results demonstrated that HBHA treatment could induce apoptosis of A549 cells. To further confirm these results, we constructed the recombinant Mycobacterium smegmatis (MS) expressing HBHA (rMS-HBHA) and explored the influence of rMS-HBHA on the function of A549 cells. rMS-HBHA infection significantly inhibited LC3 expression and the maturation of autophagosomes in A549 cells. Subsequently, we infected A549 cells with MS and detected the viability of intracellular MS by CFU counts. rMS-HBHA showed higher survival and replication capacity in A549 cells than those of the wild-type MS. Finally, infection of A549 cells with rMS-HBHA caused further apoptosis. These findings suggested that rMS-HBHA could inhibit autophagy, promote its survival and replication within A549 cells, and subsequently induce apoptosis on infected cells to facilitate infection.